Adsorption of chromium (VI) from electroplating industry wastewater by using chitosan - โตใหญ่, ศิริวารินทร์; วิไลพรเจริญ, เกตุวดี ิ; พรพัฒนกุล, ยิ่งพิศ; ปิยะมังคลา, โกวิทย์ (Frontiers in Engineering Innovation Research, 2011)
Adsorption of chromium (VI) from electroplating wastewater using chitosan as adsorbent was studied. Batch experiments were carried out as a function of the quantity of chitosan used and pH of electroplating wastewater. The experimental results show that the percentage of adsorption increased with increasing the amount of chitosan. The adsorption capacity of electroplating wastewater on 1.0 g of chitosan at pH 2.7 was 115.0 mg/g. The Langmuir, Freun dlich, Brunauer-Emmett-Teller and Temkin adsorption isotherms were applied to describe the chromium (VI) up-taking behavior. It was shown that the adsorption phenomena could be well described by Freun dlich adsorption model. The pseudo-first order and pseudo-second order were employed to determine the adsorption kinetics. It was found that the kinetic of adsorption could be elucidated by pseudo-second order. The initial rate of adsorption and half-adsorption time were 4.0 mg/g-min and 29.1 minutes, respectively. The adsorption process occurred in 2 steps. The film diffusion was the rate limiting step.